Pengaruh Arus Kas Operasi, Arus Kas Investasi, dan Arus Kas Pendanaan terhadap Profitabilitas dengan Ukuran Perusahaan sebagai Variabel Moderasi: Studi Kasus pada Perusahaan Subsektor Telekomunikasi yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2023 - Isbandriyati Mutmainah; Ichwan Rahmanu Widjaja; Minggasari Agustina (Economic Reviews Journal, 2024)
This research aims to analyze the influence of operating cash flow, investment cash flow, and financing cash flow on profitability with firm size as a moderating variable. The sample used in this study consists of companies in the Telecommunications Subsector listed on the Indonesia Stock Exchange (IDX) in 2023. This research is a causal associative study with a quantitative approach. The data used is secondary data, obtained through documentation techniques, while the sampling technique used is purposive sampling. The analysis methods employed are descriptive analysis and Moderated Regression Analysis (MRA), where profitability is the dependent variable, operating cash flow, investment cash flow, and financing cash flow are the independent variables, and firm size is the moderating variable. The results of the study indicate that operating cash flow and financing cash flow have a significant impact on profitability, while investment cash flow does not have a significant effect on profitability. The study also shows that firm size does not moderate the influence of operating cash flow, investment cash flow, and financing cash flow on profitability.